Multidisciplinary diagnosis and treatment of recurrent follicular dendritic cell sarcoma in abdomen: A case report. Issue 51 (18th December 2020) - Qu, Chang; Tian, Xiaodong; Ma, Yongsu; Xie, Xuehai; Wang, Mingyue; Dong, Yujun; Zhang, Jixin; Liu, Ping; Yang, Yinmo
Abstract: Rationale: Follicular dendritic cell sarcoma (FDCS) is a rare malignant tumor derived from follicular dendritic cells, and is often associated with Castleman disease. Here we present a rare case of paraneoplastic pemphigus (PNP) with FDCS which required multidisciplinary approach for the diagnosis and treatment. Patient concerns: A 28-year-old Chinese female had FDCS recurrence, and primary clinical manifestation was PNP. Diagnoses: PNP with FDCS. Interventions: The patient received gamma globulin infusion, took anlotinib, and underwent plasma exchange therapy. Outcomes: The skin lesions recovered and there was no evidence of tumor recurrence. Lessons: The diagnosis and management of PNP with FDCS require close cooperation among surgeons, dermatologists, hematologists, otolaryngologists, oncologists, radiologists, pathologists, and respiratory doctors. The interesting clinical manifestations of this patient provide a multifaceted approach to the investigation of the interactions among FDCS, Castleman disease, and PNP.